Transferibilidade e desenvolvimento de sistema multiplex de genotipagem de marcadores microssatélites para Pterodon emarginatus Vogel (Fabaceae) - Santana, Ariane Rolins de (2014)
Microsatellite markers are widely used to assess the genetic variability in natural populations. These markers can be developed from derived Expressed sequence tag (ESTs) or genomic libraries. A feasible and economical alternative for obtaining of these markers for species that do not already have them is the transferability from primers designed for species evolutionarily close. The species Pterodon emarginatus Vogel (sucupira) belongs to the Fabaceae family and shows great potential for use timber and medicinal, which makes them a target of exploitation. Thus, studies that contribute to their use and conservation are needed, including the genetic population. Therefore, the aim of this study was to evaluate the potential for cross-amplification primers developed for the species Phaseolus vulgaris to P. emarginatus and to analyze the polymorphism of the loci transferred from multiplex genotyping in three populations of this species. For this, were evaluated 539 primers developed for Phaseolus vulgaris, with 345 derived from ESTs libraries and 194 genomics. Amplification tests were performed using three individuals, while the assessment initial of the polymorphism with eight. Finally, genetic diversity parameters were estimated using 88 plants from three natural populations of P. emarginatus. Primers that showed amplification products visualized on agarose gel were then evaluated in 6% acrylamide gel stained with silver nitrate. Polymorphic loci were synthesized with fluorescence for evaluation and genotyping by capillary electrophoresis in ABI3500 automatic DNA analyzer. The loci were transferred to P. emarginatus 23 (4 %) being 7 polymorphic. Polymorphic, 6 electropherograms profiles. These 6 loci were evaluated in populations along with three polymorphic genomic loci previously standardized sucupira, totaling nine loci suitable for genotyping. It was possible to develop two multiplex systems, a compound of 5primers and another for 4. The number of alleles per locus ranged from two to 13, with an average of five alleles per loci. The mean values of He and Ho for both populations were 0,563 and 0,463 respectively. The value of f was not significant for the total population and equal to 0,144. The values FIT and FST were significant and equal to 0,06 and 0,195 respectively. Microsatellite markers transferred and polymorphic for P. emarginatus showed polymorphism and can be used in studies genetic population more depth to the species.